One-year results of coronary artery stenting in elderly patients - A. N. Sumin; R. A. Gaifullin; S. V. Ivanov; E. V. Korok; A. V. Shcheglova; M. G. Mos’kin; O. L. Barbarash; L. S. Barbarash (Российский кардиологический журнал, 2013)
Aim. To study the one-year survival after coronary artery stenting (CAS) across age groups and to identify the predictors of cardiovascular events registered during the follow-up period. Material and methods. In total, 662 patients who underwent CAS were divided into 4 groups: Group I – under 60 years (n=363); Group II – 60–64 years (n=140); Group III – 65–69 years (n=88); Group IV – 70+ years (n=71). The end-points, registered during the one-year follow-period, included death, myocardial infarction (MI), stroke (S), repeat revascularisation, and their combinations. In addition, the pre- and peri-intervention predictors of the abovementioned cardiovascular events were analysed. Results. Based on the one-year follow-up data, there was an insignificant increase in all-cause mortality among older patients. However, the difference in cardiovascular mortality across the groups was statistically significant (p for trend 0,04). In multivariate regression analyses, age was not independently associated with the risk of cardiovascular death, while atherogenic index, decreased left ventricular contractility, and post-intervention renal dysfunction were independent predictors of cardiovascular mortality. The independent predictors of combined end-point were circulatory support duration, peri-intervention S, and the lesions in two or more coronary arteries. Conclusion. In one year after CAS, 65–69-year-old patients demonstrated higher cardiovascular mortality levels, with no apparent increase in all-cause mortality and the incidence of combined end-point. Age was not an independent predictor of the one-year risk of cardiovascular events.